The Application of Human–Computer Interaction Technology Fused With Artificial Intelligence in Sports Moving Target Detection Education for College Athlete - Liu, Jie; Wang, Le; Zhou, Hang (Frontiers in Psychology, 2021)
The purposes are to digitalize and intellectualize current professional sports training and enrich the application scenarios of moving targets’ motion capture technology based on Artificial Intelligence (AI) and Human-Computer Interaction (HCI) in sports training. From an educational psychology perspective, sport techniques are a cognitive ability of sports and a tacit knowledge. While sports technology, language, image, and other methods play an auxiliary role in sports training. Here, a General Framework of Knowledge-Based Coaching System (KBCS) is proposed using the HCI technology and sports knowledge to accomplish autonomous and intelligent sports training. Then, the KBCS is applied to table tennis training. The athletic performance is evaluated quantitatively through calculation of the sports features, motion recognition, and the hitting stage division in table tennis. Results demonstrate that the speed calculated by the position after mosaicking has better continuity after the initial frame of the unmarked segment is compared with the end frame of the market segment. The typical serve and return trajectories in three serving modes of slight-spin, top-spin, and back-spin, as well as the trajectories of common services and return errors, are obtained through the judgment of the table tennis’ serve and receiving. Comparison results prove that the serve stability of slight-spin and back-spin is better than top-spin, and a lower serve speed has higher stability. Experimental results show that the level distribution of the three participants calculated by the system is consistent with the actual situation in terms of the quality of the ball returned and the standard of the motion, proving that the proposed KBCS system and algorithm are useful in a small sample, thereby further improving the accuracy of pose restoration of athletes in sports training.